(untitled) (International journal of medical sciences, 2026)
Fluid accumulation in the abdominal cavity is a clinical condition called ascites in medicine, which is characterized by the pathological accumulation of fluid in the peritoneal cavity. Ascites occurs as a result of various diseases and can cause serious complications. This article analyzes the etiology (causes of occurrence), pathogenesis (mechanisms of fluid accumulation), clinical manifestations and diagnostic principles of ascites. Also, the factors leading to ascites, its mechanisms of action, complications and significance are considered in detail. This article is prepared on the basis of Uzbek literature and international sources and serves as a methodological guide in clinical practice.